EXPEDIENTE - v18n3 - Tsallis, Alexandra Cleopatre; Jacó Vilela, Ana Maria; Mendes, Deise Maria Fernandes; Quadros, Laura Cristina de Toledo; Darriba, Vinicius Anciães (Estudos e Pesquisas em Psicologia, 2019)
EXPEDIENTE - v18n3